MATHEMATICAL PROBLEM SOLVING IN ADDITION AND SUBTRACTION PROBLEMS OF STUDENTS WITH LEARNING DIFFICULTIES - García Robelo, Octaviano (Atenas, 2014)
The study evaluated the efficacy of a program for conceptual comprehension to solve addition and subtraction problems for students with low achievement in mathematics, supported by the adaptation of a strategy that guided their reasoning. Participants were eleven children from 3rd and 4th grade. Students’ conceptual and algorithmic knowledge, strategy use for solving problems, and attitude toward mathematics were assessed. Results demonstrated that comprehension of the decimal system and the adaptation of a solving problem strategy improved children’s understanding of concepts and procedures related to addition and subtraction algorithms, and through this, promoted interest, comprehension for problem solving.